2006
DOI: 10.1038/sj.jp.7211490
|View full text |Cite
|
Sign up to set email alerts
|

Fewer spontaneous arousals during prone sleep in preterm infants at 1 and 3 months corrected age

Abstract: Objective: This study was performed to determine if there were fewer spontaneous arousals in prone sleep than in supine sleep.Study design: Home polysomnography/video recordings were done during daytime naps in 14 preterm infants: four at corrected age of 1 month, nine at both 1 and 3 months, and one only at 3 month. A body movement lasting 3 to 60 s during sleep was used as an indicator of spontaneous arousals.Results: Most arousals had a heart rate increase and change in respiration pattern. The mean duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 34 publications
(51 reference statements)
0
9
0
1
Order By: Relevance
“…One study [30] demonstrated less frequent arousals in premature infants when lying prone at 1-3 months of age, corrected for prematurity. The second study [31] demonstrated that although subcortical arousals were unchanged regardless of sleep position in healthy infants, the number of cortical arousals was decreased when lying prone.…”
Section: Sleep In Sudden Infant Death Syndromementioning
confidence: 97%
“…One study [30] demonstrated less frequent arousals in premature infants when lying prone at 1-3 months of age, corrected for prematurity. The second study [31] demonstrated that although subcortical arousals were unchanged regardless of sleep position in healthy infants, the number of cortical arousals was decreased when lying prone.…”
Section: Sleep In Sudden Infant Death Syndromementioning
confidence: 97%
“…Physiologic studies have found that infants are less likely to arouse when they are sleeping in the prone position. [87][88][89][90][91][92][93][94][95] The ability to arouse from sleep is an important protective physiologic response to stressors during sleep, [96][97][98][99][100] and the infant's ability to sleep for sustained periods might not be physiologically advantageous.…”
Section: Figurementioning
confidence: 99%
“…Spontaneous arousals and those in response to exogenous stimuli are affected by many factors: sleep position (3,29,37), sleep efficiency (30), prenatal exposure to cigarette smoking (28,38), and stage of development (39). It has been hypothesized that arousal impairment may play an important role in the etiology of sudden infant death syndrome (SIDS) (32,40,43,46).…”
mentioning
confidence: 99%